2015
DOI: 10.1074/jbc.m114.589838
|View full text |Cite
|
Sign up to set email alerts
|

MEF2 Transcription Factors Regulate Distinct Gene Programs in Mammalian Skeletal Muscle Differentiation

Abstract: Background: Myocyte enhancer factor 2 (MEF2) proteins are essential for skeletal muscle development and regeneration, but their diverse roles in differentiation have not been defined. Results: Individual MEF2 proteins regulate distinct gene programs in skeletal muscle. Conclusion: Certain genes are preferentially sensitive to a specific MEF2 isoform. Significance: These findings provide opportunities to modulate MEF2 isoform-sensitive genes in skeletal muscle health and disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
93
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 90 publications
(100 citation statements)
references
References 48 publications
7
93
0
Order By: Relevance
“…This has been recently described by a gene expression analysis study in muscle cells. 23 In conclusion our work reveal a novel function of MEF2C beyond its well known role in terminal differentiation. According to the classical model MEF2C does not play any specific function in growing myoblasts but is necessary to trigger the differentiation program upon differentiation stimuli.…”
Section: Discussionmentioning
confidence: 96%
See 1 more Smart Citation
“…This has been recently described by a gene expression analysis study in muscle cells. 23 In conclusion our work reveal a novel function of MEF2C beyond its well known role in terminal differentiation. According to the classical model MEF2C does not play any specific function in growing myoblasts but is necessary to trigger the differentiation program upon differentiation stimuli.…”
Section: Discussionmentioning
confidence: 96%
“…[17][18][19][20][21][22] Furthermore, recently Mef2c has been shown to regulate cell cycle related-genes in muscle cells. 23 Therefore, in the attempt to investigate this unexplored activity, we found that the level of MEF2C protein fluctuates during the cell cycle and we describe a novel mechanism by which the Anaphase Promoting Complex/Cyclosome (APC/C) ubiquitin ligase controls MEF2C abundance. The functional relevance of this mechanism during the cell cycle is suggested by the observation that ectopic expression of a MEF2C mutant, resistant to APC/C-dependent degradation, impairs entry into mitosis and cell proliferation.…”
Section: Introductionmentioning
confidence: 99%
“…Adenoviruses for Knockdown and Overexpression-Adenoviruses carrying short hairpin RNAs (shRNAs) were generated as described previously (14). The Mef2d and lacZ shRNA adenoviruses were used at a multiplicity of infection of 50 for all assays.…”
Section: Methodsmentioning
confidence: 99%
“…Western Blot Analysis-Western blots were performed as described previously (14). Antibodies included anti-GAPDH (1:1000; Santa Cruz Biotechnology, Inc.), anti-MEF2D (1:1000; BD Biosciences), anti-proliferating cell nuclear antigen (PCNA) (1:2000; Cell Signaling), PTEN (1:1000; Cell Signaling), Akt (1:1000; Cell Signaling), pAkt Thr-308 (1:1000: Cell Signaling), pAkt Ser-473 (1:1000: Cell Signaling), cyclin D1 (1:1000; Cell Signaling), cyclin D3 (1:1000; Cell Signaling), and CDK2 (1:1000; Cell Signaling).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation